Insights into the chemical characteristics of atmospheric aerosols from urban-industrial and rural sites in south-east of Poland during winter - Szwed, Mirosław; Kozłowski, Rafał; Żukowski, Witold; Mbengue, Saliou; Suchánková, Lenka; Prokes, Roman (Quaestiones Geographicae, 2023)
This study focusses on a short-term characterisation of atmospheric aerosols from three locations in south- east of Poland with different land use characteristics, population density and sources of pollution (Katowice: urban-industrial; Strzyżowice near Lublin: rural; Kielce: urban). Twenty-four hour PM2.5 and PM10 samples were collected on the quartz filter and their chemical compositions were monitored and measured using OCEC thermo-optical analysis and scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDS). The highest concentrations of PM2.5 and PM10 were measured at the urban-industrial area in Katowice (29.6 µg ∙ m−3 and 31.0 µg ∙ m−3, respectively), whereas the highest organic carbon (OC) and elemental carbon (EC) levels were observed at the Kielce urban site (23.3 ± 4.2 µg and 3.6 ± 0.3 µg, respectively). The lowest values were obtained at the rural site for PM2.5 (10.4 ± 2.7 µg ∙ m−3) and PM10 (11.8 ± 2.7 µg ∙ m−3) and for OC (17.8 ± 1.6 µg) and EC (1.0 ± 0.1 µg). SEM-EDS analysis of samples from Kielce allows identification of internal chemical mixtures of carbon, silicon, calcium, chlorine, sodium and aluminium.